2012
DOI: 10.1159/000341877
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Salivary Ghrelin Response to a Psychosocial Stress Is Enhanced in Symptomatic Patients with Bulimia Nervosa: A Pilot Study

Abstract: Background: Stress is a precipitating factor for both binge eating and bulimia nervosa (BN); however, the biological mechanisms through which it may trigger binge eating are poorly understood. There is evidence that the adrenal hormone cortisol and the gastric peptide ghrelin might be involved in stress-induced food ingestion. We hypothesized that symptomatic patients with BN might disclose deranged responses of ghrelin and/or cortisol to stressors and that this could be related to their binge-eating behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 65 publications
3
26
1
Order By: Relevance
“…Investigations on major depression cases show constant level for ghrelin [2] . Findings of present study for ghrelin levels of depressed (CMS) animals (Table 2) are in agreement with Chuang and Zigman [17] , Asakawa et al [19] , Kristenssson et al [20] and Monteleone et al [24] reports witch indicate that ghrelin can increase in chronic psychological or environmental stress, and various protocols for depression induce.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Investigations on major depression cases show constant level for ghrelin [2] . Findings of present study for ghrelin levels of depressed (CMS) animals (Table 2) are in agreement with Chuang and Zigman [17] , Asakawa et al [19] , Kristenssson et al [20] and Monteleone et al [24] reports witch indicate that ghrelin can increase in chronic psychological or environmental stress, and various protocols for depression induce.…”
Section: Discussionsupporting
confidence: 91%
“…Another evidence for regulatory role of ghrelin in stressful condition is that ghrelin elevation occures along with epinephrine raises induced with stress [23] . Monteleone et al [24] reported considerable increase in salivary ghrelin following social stress protocol. Investigations on major depression cases show constant level for ghrelin [2] .…”
Section: Discussionmentioning
confidence: 98%
“…In recent studies, both intravenous ghrelin infusions (51) and fasting ghrelin levels (52) were positively correlated with neural responses elicited by pictures of palatable food shown to healthy volunteers during functional magnetic resonance imaging, particularly in brain regions implicated in areas that control appetitive behavior. These studies support the notion that, in accordance with the affect-regulation model, the ghrelin rise we observed after stress exposure could lead to increased food intake as an attempt to replace negative emotions with the rewarding, positive feelings of pleasure achieved by the ingestion of food (33). …”
Section: Discussionsupporting
confidence: 88%
“…In a recent study, there was a significantly longer and greater salivary ghrelin increase in patients with BN compared with controls after the TSST (33), although it is unclear to what extent salivary ghrelin reflects circulating ghrelin. In the same study, the authors did not observe differences in cortisol levels after TSST in patients with BN compared with controls (33). In a previous study from our group, we found a trend for increased cortisol levels and hunger ratings after CPT in BED compared with non-BED (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation